Non-invasive cryolipolysis™ for subcutaneous fat reduction does not affect serum lipid levels or liver function tests - Klein, Kenneth B.; Zelickson, Brian; Riopelle, Jeffrey G.; Okamoto, Eric; Bachelor, Eric P.; Harry, Rosemary S.; Preciado, Jessica A. (Lasers in surgery and medicine, 2009)
Background and Objective Cryolipolysis provides a method of non‐invasive fat reduction that significantly reduces subcutaneous fat without injury to adjacent tissues. Preliminary animal and human data have suggested that cryolipolysis has no effect on serum lipid profiles or liver tests. This study was intended to more fully document any effect of this procedure on lipid and liver‐related blood tests. Study Design/Materials and Methods Forty subjects with fat bulges on their flanks (“love handles”) were treated bilaterally with a non‐invasive device (Zeltiq Aesthetics, Pleasanton, CA) that precisely cools tissue to achieve a reduction in the fat layer. Serum lipid levels and liver tests were measured prior to treatment, and at 1 day and 1, 4, 8, and 12 weeks post‐treatment. Results No meaningful changes in mean values were observed for any blood lipid level or liver test at any point over the 12‐week follow‐up period. Conclusion Cryolipolysis, when used for reduction of subcutaneous flank fat, is not associated with changes in serum lipids or liver test results. Lasers Surg. Med. 41:785–790, 2009. © 2009 Wiley‐Liss, Inc.